2014
DOI: 10.1186/1129-2377-15-46
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic and tri-allelic 5-HTTLPR polymorphisms and triptan non-response in cluster headache

Abstract: BackgroundTriptans are only effective in terminating cluster headache (CH) attacks in 70-80% of patients. Pharmacogenetic aspects of the serotonin metabolism, specifically variation in the 5-HTTLPR may be involved.MethodsGenetic association study in a well-defined cohort of 148 CH patients with information on drug response to triptans. CH was diagnosed according to the criteria of the International Headache Society. Genotypes of the 43-bp insdel (rs4795541) and A > G (rs25531) polymorphisms in the 5-HTTLPR pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…However, another study suggested the splice variant is biologically inactive, since it did not modulate N-type Ca 2+ or G protein-gated inwardly rectifying K channels, unlike its wildtype counterpart in rat sympathetic neurons (104). In a genetic association study with 148 CH patients, variants in the serotonin-transporter-linked polymorphic region ( 5-HTTLPR ), a promoter region of the primary serotonin transporter, encoded by the SLC6A4 gene, which clears serotonin from the synaptic cleft, were studied by restriction fragment length polymorphism (RFLP) analysis (105). No association was found between the two variants investigated (a 43-bp indel (rs4795541), and an A > G SNP (rs25531)) with response to triptans.…”
Section: Genetics Of Cluster Headachementioning
confidence: 99%
“…However, another study suggested the splice variant is biologically inactive, since it did not modulate N-type Ca 2+ or G protein-gated inwardly rectifying K channels, unlike its wildtype counterpart in rat sympathetic neurons (104). In a genetic association study with 148 CH patients, variants in the serotonin-transporter-linked polymorphic region ( 5-HTTLPR ), a promoter region of the primary serotonin transporter, encoded by the SLC6A4 gene, which clears serotonin from the synaptic cleft, were studied by restriction fragment length polymorphism (RFLP) analysis (105). No association was found between the two variants investigated (a 43-bp indel (rs4795541), and an A > G SNP (rs25531)) with response to triptans.…”
Section: Genetics Of Cluster Headachementioning
confidence: 99%
“…The detailed flowchart of literature review process and reasons for study exclusion is shown in Figure 1. Among the 27 studies included in this review, 13–17,20–23,25,32–48 23 candidate gene association studies 13–17,20–23,32–40,42–46 and one GWAS 41 investigated the association of gene polymorphisms with CH susceptibility, whereas four studies using a candidate gene approach evaluated the association with treatment response in patients with CH 17,25,47,48 . Main participants’ characteristics, gene variants analyzed, and positive findings of the included studies are shown in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…Among the four studies evaluating the association between genetic variants and treatment response in patients with CH, 17,25,47,48 two studies including a total of 174 responders and 54 nonresponders investigated the association of GNB3 rs5443 with clinical response to triptans 17,25 5) showed an association of rs5443 with treatment response under the dominant genetic contrast (CT+TT vs. CC, OR: 1.96, 95% CI: 1.04–3.72, p = 0.038; Figure 5A), but not under the recessive (TT vs. CT+CC, OR: 0.38, 95% CI: 0.14–1.02, p = 0.055; Figure 5B) or the allelic contrast (T vs. C, OR: 1.20, 95% CI: 0.74–1.97, p = 0.459; Figure 5C).…”
Section: Resultsmentioning
confidence: 99%
“…However, most of these studies include only a small number of patients and may be underpowered. The positive associations found with genetic variants in the serotonin transporter have recently not been replicated [142]. A few studies have also considered medication overuse headache as a potential pharmaco-genetic interaction and have found association between this disorder and genetic polymorphisms in the dopamine neurotransmitter system (DAT, MAOA, DRD4, DRD2) and the BDNF [143][144][145] known to predispose patients to drug abuse behaviour.…”
Section: Headachementioning
confidence: 99%